Strategic alliance in municipal savings banks to improve profitability: A case study - Del Castillo Miranda, Victor Manuel; Sagástegui Cruz, Julia Otilia; Del Castillo Sagastegui, Mairano José (LACCEI, 2024)
The purpose of this study was to design strategic alliances between supply chain companies and entities in the microfinance sector. Companies in this sector depend on the creation of innovative strategies in order to overcome the difficult competition they face, even more so after the context brought by COVID-19. The alliance was designed for three EMs belonging to different geographical locations. : Caja del Santa- North Coast, Caja Ica- South Coast and Caja Maynas- Selva. The methodological design was a qualitative, descriptive, and case study research. The data collection technique was interviews carried out with the Management Committees and as an instrument, interview guides and an evaluation questionnaire were used, and information was also taken from the Low Banking Zones (ZBB) to intervene. The target indicators of the Alliance's Strategic Maps were presented, and the interviews were coded and analyzed using the ATLAS.ti software. The main conclusions are that the Management Committees positively appreciate the alliance to achieve greater capitalization (ROE) and that the internal and financial capabilities of each EM will be critical for the success of the alliance.